'Teachers' to 'academics': the implementation of a modernisation project at one UK post-92 university. Issue 7 (2nd July 2016) - Hunt, Clive
Abstract : Among the many external forces that have impacted upon institutions, league tables have been the dynamic to which universities across the world are now responding. Following the appointment of a new vice-chancellor at one post-92 UK university, a modernisation project was introduced aimed at maximising the institutions' research standing. For the institutional actors, the university's lecturers, this modernisation project demanded a change in their working practices from one which had focused on teaching-related activities to a situation where an emphasis was to be placed upon research. This study examines how university teachers at this institution understood and responded to the modernisation project to acquire research skills and provides an insight into a path-breaking strategic plan that was enacted within a historically dependent setting. It muses on the dialectics of institutional path dependency and the path-breaking effect of a modernisation project that was stimulated by new managerialism.